Study and analysis of thin film contact behaviours in micro/nano devices - Huang, Zhongwei. (2011)
Today’s nano scale technologies in wireless communication, microwave communication and other high value applications depend on RF MEMS technology to solve many intriguing problems. The competitive and inspiring developments of miniaturized communication devices strained the market to acquire efficient devices, this made possible only by advancing through RF MEMS technology.